2020
DOI: 10.1101/2020.10.30.20223180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk perceptions and preventive practices of COVID-19 among healthcare professionals in public hospitals in Ethiopia

Abstract: Healthcare professionals are at higher risk of contracting the novel coronavirus due to their work exposure in the healthcare settings. Practicing appropriate preventive measures to control COVID-19 infection is one of the most important interventions that healthcare workers are expected to use. The aim of this study was to assess the level of risk perception and practices of preventive measures of COVID-19 among health workers in Addis Ababa, Ethiopia. A hospital-based cross-sectional study was conducted fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Gaps and negligence in applying the COVID-19 preventive measures among the public have been observed. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Gaps and negligence in applying the COVID-19 preventive measures among the public have been observed. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“… 9 – 11 However, low-resource countries like Ethiopia were experiencing multilevel barriers to preparedness due to limited resources and weak health care infrastructure. 12 , 13 HCWs’ inadequate preparedness (24%–57%) 14 to respond to an outbreak contributes to workers leaving their positions due to fear of infection and community distrust of government and HCWs. 15 17 Being a nurse, female, having an isolated ward, knowing COVID-19 management, good communication with management, and work experience >10 years had association with the PPE utilization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to moderate to severe psychological problems, HCWs reported a high rate of perceived vulnerability for COVID-19 infection 29 and were worried about the risk of becoming infected with the virus and the risk of transmitting it to their families. 60 As a result, most (97%) of the HCWs reported that they were not ready to give care for COVID-19 patients. 21 …”
Section: Resultsmentioning
confidence: 99%